Messages, Meanings and Symbols: The Communication of Information - Meadow, Charles T. (Rowman & Littlefield Publishers, 2006)
A deep and penetrating exploration of the key concepts of information and communications sciences by one of its founders, this book covers everything in its subject that you want to know more about including the bedrock topics of signs, symbols, information, and communication, all considered from an historical and foundational perspective that is satisfying to the beginning student and worthwhile for practitioners of long standing. All the major players are given their role, from Shannon and Weaver to Tim Berners-Lee, with Marshall McLuhan an engaging participant. Communication in all its forms—be it print or electronic media, mass communication as well as person-to-person messaging, whether by mail, telephone, gesture, or email—is thoroughly examined in this book, which can serve as either an introductory text to undergraduates in information science, an interesting read for the layman, or as a refresher for the communications professional.